Injury and Accumulation: Making Sense of the Punishing State - De Lissovoy, Noah (Social justice, 2015)
The article talks about progressive carceralization in contemporary U.S. society, the institutionalization of abuse and torture, and state violence in the context of capitalism and social production. Topics include the Marxist theory in relation to coercion and capital accumulation, violence in capitalism, and the articulations between capitalist exploitation and racism. Other topics include punishment and permanent war in a neoliberal society, and a principle of violation in state violence.